Comparison of Media and Source Framing in Selected Chinese Newspaper Stories on Bilingual Education Issues in Malaysia - Chang, Peng Kee (2009)
Framing study is getting more popular among the communication scholars. Many studies have been conducted to examine the frame building from the outlook of media framing rather than source framing. The role of news sources as an external factor in the frame-building process has thus far very much been neglected. The scrutiny of news sources – government, ruling political parties, education movement and interest groups, opposing political parties, general public, and editorial – for their predominant generic frames is believed to have made significant contribution to the school of framing study. This empirical research aims at comparing the framing of news stories by both newspapers and news sources. In addition, these two communication elements are to ascertain their relationships with news slants. Content analysis will be employed to meet the above research objectives. Five Chinese daily newspapers that are available at the research location are selected and their coverage on the educational issue of teaching and learning of mathematics and science subjects in two languages is chosen as it is thought to be relevant to the Malaysian Chinese community. Two significant events in this bilingual educational issue have been identified, i.e. the first announcement of using English as the medium of instruction for these two subjects by the then Prime Minister Mahathir Mohamad in 2002 and the announcement of retaining the examination format for 2008 Primary School Achievement Test by the then Prime Minister Abdullah Ahmad Badawi in 2007. The sampling procedure applies a three-week period after the abovementioned announcements by the country premiers. All paragraphs pertaining to the issue during the study periods are taken into scrutiny. A total of 2,374 units of analysis have been measured for the visibility of five predetermined generic frames. Source frames have been ascertained to emerge by means of favourable frame prominently portrayed by various news sources, who act as frame sponsors in building the news stories. The findings of this research profoundly claim that source frames do exist and they have more impact than media frames. Sources of information initiate and promote a certain frame in the news while media workers depend on the situation to quote the sources with both objective and subjective judgements for newsworthiness. In other words, the existence of frames in any news story is indeed crafted by sources while the media workers just process and get them printed on paper. In addition, the research results reveal that news sources are found to coalesce by way of slanting their news directions. This pattern of news slants is maintained throughout different periods.